Dilema Hak Cipta: Lagu Live di Kafe vs Perlindungan Pencipta - Febriani Inggrit Risamena; A. Sakti R.S. Rakia; Masrifatun Mahmudah (Jurnal Litigasi Amsir, 2024)
This study examines the legal protection for songwriters who sing live in cafes based on Law No. 28 of 2014 concerning Copyright. Using empirical juridical methods, this study examined secondary and primary data. The results of the study show that the use of live music is regulated in the Copyright Law and Government Regulation No. 56 of 2021, which requires permission and royalty payments to copyright holders. Legal protection can be enforced through alternative dispute resolution, litigation, or criminal prosecution to prevent and minimize copyright infringement.